2009
DOI: 10.1016/j.joca.2008.05.007
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1 regulation of type II collagen and MMP-13 expression in rat endplate chondrocytes via distinct signaling pathways

Abstract: In rat endplate chondrocytes the PI3K pathway mainly transduces IGF-1 effect on col2 expression while the ERK pathway mediates IGF-1 effect on MMP-13 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
58
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 30 publications
3
58
0
2
Order By: Relevance
“…IGF1 inhibited IL-1β-induced activation of NF-kB and apoptosis of chondrocytes partly through inhibiting phosphorylation, degradation and kinase activity of IkBα, which consequently inhibited NF-kB-mediated expression of some inflammation- and apoptosis-related genes [33], [41]. Meanwhile, IGF-1 also helped to retain the typical features in chondrocytes and enhances synthesis and release of PGs and collagen II mainly through activation of PI3K/Akt signaling pathway [29], [41], [42].…”
Section: Discussionmentioning
confidence: 99%
“…IGF1 inhibited IL-1β-induced activation of NF-kB and apoptosis of chondrocytes partly through inhibiting phosphorylation, degradation and kinase activity of IkBα, which consequently inhibited NF-kB-mediated expression of some inflammation- and apoptosis-related genes [33], [41]. Meanwhile, IGF-1 also helped to retain the typical features in chondrocytes and enhances synthesis and release of PGs and collagen II mainly through activation of PI3K/Akt signaling pathway [29], [41], [42].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the cellular interactions between chondrocytes and BMSCs in monolayer co-culture are likely to be bi-directional. Chondrocyte-secreted factors such as TGF-β, bone morphogenetic proteins and IGF-I may promote chondrogenesis of BMSCs in vitro (35)(36)(37). Yamamoto et al (38) co-cultured nucleus pulposus cells with mesenchymal stem cells and found that mesenchymal stem cells can enhance secretion of TGF-β, IGF-1 and epidermal growth factors from nucleus pulposus cells.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of MMP-13 is regulated by MAPKs, NF-jB, and Smad2/3 signaling pathways [42,43]. Among them, ERK1/2, JNK, and p38 [11][12][13] are mainly involved in signaling transduction during the inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, ERK1/2, JNK, and p38 [11][12][13] are mainly involved in signaling transduction during the inflammatory process. It was reported that [43] in rat endplate chondrocytes, PI3K pathway was involved in the expression of type-II collagen while ERK pathway was involved in the expression of MMP-13. The pomegranate fruit extract (PFE) was reported [44] to inhibit the expression of MMP-13 in the OA cartilage via NF-jB and JNK/p38.…”
Section: Discussionmentioning
confidence: 99%